Mechanochemical Synthesis of Fluorapatite-Zinc Oxide (FAp-ZnO) Composite Nanopowders. (2nd September 2012) - Nasiri-Tabrizi, Bahman; Fahami, Abbas
Abstract : Fluorapatite-zinc oxide (FAp-ZnO) composite nanopowders were successfully prepared via mechanochemical process. Characterization of the products was carried out by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR) analysis, energy dispersive X-ray spectroscopy (EDX), and field-emission scanning electron microscopy (FE-SEM) techniques. Results revealed that in the absence of ZnO which produced by hydrothermal method, the single-phase FAp had high-crystalline structure with appropriate morphological features. Furthermore, after 5 h of milling in the presence of 5 wt.% ZnO, FAp-5 wt.% ZnO, composite nanopowders with no impurity phase was obtained. Structural studies illustrated that the milling up to 5 h was not accompanied by a remarkable change in the structural features. Moreover, the gained composite powders presented an average crystallite size of about 40 nm for FAp. The FE-SEM observations indicated that the experimental outcome had a cluster-like structure which consisted of several small particles. Finally, results propose a new approach to prepare commercial amounts of novel FAp-based composite nanopowders with high quality and suitable structural and morphological features.